Application of a guided inquiry learning model assisted by a student worksheet to improve high school students analytical skills - Lelitya Nurmawati; Dian Novita (Jurnal Pijar Mipa, 2022)
This study aims to determine the guided inquiry learning model's implementation effect on students' activities, students' analytical skills, and student responses on the reaction rate material. This study used the one-group pretest-posttest design. The subjects in this study were students of the eleventh grade of IPA 1 at SMA Kemala Bhayangkari 1 Surabaya. The instruments used include learning model implementation sheets, student activity sheets, analytical ability test sheets, and student response questionnaires. The results showed that (1) the quality of the guided inquiry learning model application during two meetings from phase one to six are in very good criteria. (2) The activities of students in two meetings have the percentage of activity time related to analyzing at the first and second meetings of 77.2% and 81.99%, respectively. (3) The results of the analysis ability of students with a percentage gain score are 85.81% on the high criteria. (4) The percentage of student responses, 87%, agrees that learning using the guided inquiry learning model can train and improve analytical skills.